Mitochondrial dysfunction and fatigue in Sjögren’s disease - Astrid Rasmussen; Christopher J Lessard; A Darise Farris; Kristi A Koelsch; Biji T Kurien; Joshua Cavett; Kathy Sivilis; Robert Hal Scofield; John Aubrey Ice; Rebecca A Wood; Gavin Pharaoh; Valerie Lewis; et al. (RMD Open)
Objective Sjögren’s disease (SjD) is a chronic exocrine disorder typified by inflammation and dryness, but also profound fatigue, suggesting a pathological basis in cellular bioenergetics. In healthy states, dysfunctional mitochondria are recycled by mitophagic processes; when impaired, poorly functioning mitochondria persist and produce inflammatory reactive oxygen species. Employing a case–control study, we tested our hypothesis that mitochondrial dysregulation in T cells is associated with fatigue in SjD.Methods We isolated pan T cells from peripheral blood mononuclear cells of 13 SjD and 4 non-Sjögren’s sicca (NSS) subjects, who completed several fatigue questionnaires, along with 8 healthy subjects. Using Seahorse, we analysed T cells for mitochondrial oxygen consumption rate (OCR) and extracellular acidification rate, which we assessed for correlation with fatigue measures. Using public microarray data available for 190 SjD and 32 healthy subjects, we identified a mitophagic transcriptional signature that stratified SjD patients into 5 discrete clusters. Comparisons between the SjD subjects in these clusters to healthy individuals identified differentially expressed transcripts, which we subjected to bioinformatic interrogation.Results Basal OCR, ATP-linked respiration, maximal respiration and reserve capacity were significantly lower in SjD and NSS subjects compared with healthy individuals, with no differences in non-mitochondrial respiration, basal glycolysis or glycolytic reserve. Scores related to a sleep questionnaire and Bowman’s Profile of Fatigue and Discomfort showed correlation with altered OCR in SjD. Subgroup differential expression analysis revealed dynamic transcriptional activity between mitophagy subgroups, expanding the number of differentially expressed transcripts tenfold.Conclusions Mitochondrial dysfunction and fatigue are significant problems in SjD warranting further investigation.